A case of anti-mitochondrial M2 antibody (AMA M2) positive AIH confused with PBC-AIH overlap syndrome - Fukasawa, Yuichiro; Umemura, Machiko; Nagasaka, Atsushi; Higuchi, Akifumi; Endo, Ayana; Fujita, Yomo; Nakamura, Michio; Nishikawa, Shuji (Kanzo, 2013)
A 71-years-old woman visited us in March 2011 for moderately abnormal levels of biliary enzymes developed from January 2011. The patient was diagnosed as asymptomatic primary biliary cirrhosis (PBC) because of abnormal level of biliary enzymes and a presence of anti-mitochondrial M2 antibody (AMA M2). The patient accused thick urine and malaise from April 2011. Blood sample collected at April 13 revealed 3.7 mg/dl of T-bilirubin and an abrupt increase of transaminases such as 224 IU/L of AST and 1095 IU/L of ALT. Interface hepatitis and hepatoocytic necrosis were found in liver biopsy specimen. Proliferation of bile ductules was remarkable, but destruction of bile ducts was minimal at the portal area. Based on these findings, the patient was diagnosed as autoimmune hepatitis (AIH) with positive AMA M2. Liver function rapidly recovered by the treatment of UDCA (ursodeoxycholic acid) (600 mg/day) and prednisolone (PSL; 30 mg/day), and the treatment level of PSL was gradually reduced thereafter. The patient is currently under clinical follow-up without deterioration of liver function.